If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + -17 = 4(1 + -5n) Reorder the terms: -17 + N = 4(1 + -5n) -17 + N = (1 * 4 + -5n * 4) -17 + N = (4 + -20n) Solving -17 + N = 4 + -20n Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + N = 4 + 17 + -20n Combine like terms: -17 + 17 = 0 0 + N = 4 + 17 + -20n N = 4 + 17 + -20n Combine like terms: 4 + 17 = 21 N = 21 + -20n Simplifying N = 21 + -20n
| 3(x-7)/2=15 | | (3.4x)+7=x+54.6 | | 2x+4x-9+x^2+2x+9=180 | | 0=x^2+13x+30 | | 13n=.26 | | 3x-1=0.50(4x+6) | | 6x^2+36+48=0 | | -7x-8=4x+6 | | 4/13p=-16/5 | | -8/3÷3 | | -18=0(-3)+b | | -5/6(6)=x | | -17=0(-2)+b | | -21x+7=14 | | 550-30y/50 | | -5/6y=1 | | M=-0.711A+206.6 | | 1.50b=31.50 | | 2x^2=-21x | | -3.5x=9.2 | | 5/6x72/5 | | 17=0(-2)+b | | -5/6y=0 | | 21x(2/7)=6 | | -4.3x=-8.6 | | F(x)=x^4-4x^3-9x^2+36 | | 0.2x-0.5x-3=18 | | -3x-14=y | | y^2+54=0 | | 17+33x=5 | | -3x+7(2)=-16 | | -x=59 |